2012
DOI: 10.1007/s12350-012-9533-x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the side effect profile of regadenoson: A randomized double-blinded placebo-controlled study with aminophylline in patients undergoing myocardial perfusion imaging. “The ASSUAGE trial”

Abstract: This trial supports the routine administration of IV-aminophylline to reduce the frequency and severity of adverse effects associated with regadenoson-stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 14 publications
0
23
1
Order By: Relevance
“…8 Since the approval of regadenoson, multiple prospective studies have reported safety data for regadenoson alone and in combination with exercise and have examined its safety in special populations such as patients with kidney disease and pulmonary disease. [9][10][11][12][13][14][15][16] These studies combined had data on *2,300 patients that received regadenoson and reported no deaths or MIs. In an on-going multi-center phase 3b study examining the administration of regadenoson following inadequate exercise stress test compared to regadenoson alone (ClinicalTrials.gov identifier NCT 01618669) that has enrolled more than 1,000 patients, one patient had an acute coronary syndrome following regadenoson administration.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…8 Since the approval of regadenoson, multiple prospective studies have reported safety data for regadenoson alone and in combination with exercise and have examined its safety in special populations such as patients with kidney disease and pulmonary disease. [9][10][11][12][13][14][15][16] These studies combined had data on *2,300 patients that received regadenoson and reported no deaths or MIs. In an on-going multi-center phase 3b study examining the administration of regadenoson following inadequate exercise stress test compared to regadenoson alone (ClinicalTrials.gov identifier NCT 01618669) that has enrolled more than 1,000 patients, one patient had an acute coronary syndrome following regadenoson administration.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Initial large-scale trials using regadenoson either excluded patients with known bronchospastic/bronchorestrictive lung disease or only allowed for inclusion of a small fraction of patients with known COPD or asthma (range 6%-16%). 4,35,39,40 Following initial post-marketing reports of wheezing, dyspnea, and respiratory arrest, 16 the use of regadenoson in patients with COPD and/or asthma was examined in randomized, double-blinded, cross-over, placebo-controlled trials that included patients with moderate-severe COPD (RegCOPD) and mild-moderate asthma (RegAsthma). 41,42 These showed that use of regadenoson in the above patient subgroups was well tolerated without significant changes in respiratory rate, FVC, FEV1, new-onset wheezing, or bronchoconstriction and oxygen saturation compared to placebo.…”
Section: Non-cardiovascular Adverse Effectsmentioning
confidence: 99%
“…4,35,39,40 These adverse effects occur more frequently in patients with advanced renal disease. 39,40 With the exception of diarrhea, these are short-lived, and can be easily managed conservatively.…”
Section: Non-cardiovascular Adverse Effectsmentioning
confidence: 99%
“…A remarkable finding of the ASSUAGE trial has been the high degree of patient satisfaction associated with routine reversal of regadenoson with aminophylline, with 91% patients receiving aminophylline reversal indicating they would definitely or probably be willing to repeat the test. 6 Prior to the ASSUAGE-CKD Trial, safety concerns existed for the potential of serious adverse events associated with reduced excretion, enhanced exposure, and toxicity of regadenoson. These concerns seemed justified on the basis of the triphasic half life of regadenoson with a 2-hour terminal elimination phase of regadenoson and with urinary elimination of 57% of administered regadenoson as unchanged drug.…”
Section: See Related Article Pp 112-118mentioning
confidence: 99%
“…7 Indeed, patients with CKD and ESRD demonstrate reduced clearance of regadenoson and are exposed to the regadenoson for a longer periods of time which likely explains the finding of greater prevalence of headaches and minor gastrointestinal adverse effects including diarrhea and abdominal discomfort which were substantially reduced with prophylactic administration of aminophylline, which competitively inhibits A2a receptor activation and associated coronary vasodilation compared to placebo-treated patients. 6,8 In the ASSUAGE-CKD trial, routine standardized administration of intravenous 75 mg aminophylline 90 s post-radioisotope injection in all patients with severe CKD substantially reduced the frequency of any prespecified adverse event, diarrhea and headache, and severity of the adverse effects associated with regadenoson-stress and was better tolerated in the aminophylline group without changing the ischemic burden. 9 Thus, with prompt routine reversal of regadenoson with administration of aminophylline, regadenoson vasodilator SPECT MPI is safe and well tolerated in patients with ESRD without increased risk of serious adverse events.…”
Section: See Related Article Pp 112-118mentioning
confidence: 99%